2015
DOI: 10.1039/c5ra02684a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Yasuda parameter for the atmospheric plasma deposition of allyl methacrylate

Abstract: This work studies the influence of the proportional change in discharge power and the monomer feed on the morphology and the chemistry of atmospheric plasma deposited films. Atmospheric plasma coatings of allyl methacrylate were deposited using dielectric barrier discharge plasma under different conditions but always under the same ratio between the discharge power and monomer feed (W/FM). It is shown that a constant W/FM does not necessarily provide the same chemistry and the same morphology for atmospheric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
(75 reference statements)
2
29
0
Order By: Relevance
“…100–150 nm in thickness, covered by a rough top layer comprising densely grouped columnar or globular features of variable height, between 200 and 400 nm. Similar micrographs of PP AMA coatings were reported elsewhere, morphologies that suggest “powder” formation in the gas phase. In other words, this does not come as a surprise, but is a quite well‐known characteristic when highly reactive monomers like AMA or acetylene are involved …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…100–150 nm in thickness, covered by a rough top layer comprising densely grouped columnar or globular features of variable height, between 200 and 400 nm. Similar micrographs of PP AMA coatings were reported elsewhere, morphologies that suggest “powder” formation in the gas phase. In other words, this does not come as a surprise, but is a quite well‐known characteristic when highly reactive monomers like AMA or acetylene are involved …”
Section: Resultssupporting
confidence: 83%
“…Parameters Ψ and Δ were determined at 25°, 35°, and 45° incidence angles using a J. A. Woollam RC2 ® instrument operating in the 193–1700 nm wavelength range, and were interpreted using CompleteEASE™ software and an optical model consistent with the SEM observations from (2) above …”
Section: Methodsmentioning
confidence: 99%
“…The highest amino groups content was obtained for conditions using the highest precursor flow rate. This behavior is consistent with the so‐called Yasuda's parameter (W/FM) but its validity was recently criticized due to the intrinsic non‐homogeneity of atmospheric plasma . The results were interpreted by using the comparison with post‐treated and ‐grafted APTES coatings.…”
Section: Resultssupporting
confidence: 56%
“…Allyl methacrylate has a methacrylic and allylic C5 5C double bond and has been used as precursor in an atmospheric DBD reactor for the production of pdAMA films. [26][27][28][29] Based on FTIR, XPS, and solid state 13 C NMR, it was concluded that highly cross-linked pdAMA films were obtained. In comparison to AMA, the plasma deposition rate of the analogous fully saturated PiB was found to be four times lower at a constant Yasuda factor (Y f , in kJ g À1 ), i.e., input plasma power (in W) per precursor mass feed rate (in mg s À1 ).…”
Section: Introductionmentioning
confidence: 98%